PARADIGMA DESIGNULUI ÎN ACTIVITATEA BIBLIOTECONOMICĂ - KULIKOVSKI, Conferențiar universitar , Lidia (BIBLIOPOLIS, 2020)
The deep changes in the last decade have imposed the need to revive, reinvent the infodocumentary environment. The public libraries need to take a new way, to create new services innovative and valuable. The approach of the design paradigm in the library activity is built on the supposition that the design thinking transform libraries and inspiries innovation. The „B.P. Hasdeu” Municipal Library is the institution that understands the design. The library uses the transforming design, the design that brings users and leads the library to new dimensions. The author demonstrates that the library is responsive to the design by presenting examples. And the people outside the library recognize the design thinking in the library activity. The article provides to the librarians a set of necessaries tools to help them to implement the design in library activity.